Síntese de 2-amino(alcoxi)-5-trifluoracetil-1,2,3,4-tetraidropiridinas e oxazolo[3,2-a]piridinas - Fernandes, Liana da Silva (2006)
The present work describes the synthesis of novel 2-alkoxy-5-trifluoroacetyl-1,2,3,4-tetrahydropyridines, 2-amino-5-trifluoroacetyl-1,2,3,4-tetrahydropyridines and oxazolo[3,2-a]pyridines from the cyclocondensation reactions between 2-alkoxy-5-trifluoroacetyl-2H-3,4-dihydropyranes and aminomethyl pyridines, aminoalcohols and o-aminophenol, respectively, in good yields (72-96%). The 2-alkoxy-5-trifluoroacetyl-1,2,3,4-tetrahydropyridines were synthesized using stoichiometric amounts of the trifluoroacetyl dihydropyranes and three different aminomethyl pyridines. When the reactions were carried in an one molar excess of the aminomethyl pyridines the 2-amino-5-trifluoromethyl-1,2,3,4-tetrahydropyridines were isolated as single products. Finally, the oxazolo[3,2-a]pyridines were obtained from the cyclocondensation reactions between equal molar quantities of the trifluoroacetyl dihydropyranes and three different aminoalcohols and oaminophenol.